Ambivalent Assets: The Success of Sand-Storage Dams for Rainwater Harvesting in Kitui County, Kenya - Ertsen, M. W.; Ngugi, K. N. (Frontiers in Water, 2021)
This paper assesses the success of sand-storage dams in Kitui, Kenya – with “success” being considered to relate to the amount of water that dams can store, and the usability of the water in terms of access, quantity and quality. Building on a series of recent larger and smaller research projects, the paper sketches the complex interactions between community involvement, water use, and hydrological processes. Catchment-wide processes (including infiltration and runoff) resulting in water retention and sustained flow in the seasonal rives need to be taken into account. At the same time, within a catchment and within communities, diversity between water users (for example in terms of access or values related to water) will be encountered. The interplays between all these different issues have to be studied in more detail, to support governments and communities developing water harvesting interventions like sand-storage dams.